Oral and dental health comorbidity in COVID-19 era: social aspects and impacts on community dentistry in Saudi Arabia - Alshammari, Abdullah Faraj; Sadoon, Abdulmjeed; Aldakhil, Ahmed Mohmmed; Alotaibi, Alanoud Naif; Alturki, Rawan Turki (International Journal Of Community Medicine And Public Health, 2020)
Background: The World Health Organization (WHO) announced COVID-19 a public health emergency of global concern. The most vulnerable populations are elderly and/or medically compromised people. it is recommended that non-emergency and elective procedures be postponed while dental clinics remain open to patients with urgent needs. Providing oral-health instruction is important to limit the needs of patients to leave their homes for treatment. The aim of this study is to evaluate the knowledge and behaviour of residents in Saudi Arabia towards their oral health during the COVID-19 outbreak. Methods: This study was a cross-sectional descriptive survey. Data was collected through online self-administration of the questionnaire on the Google forms platform. Any relationships between the variables were analysed using Pearson’s chi-squared test. A p value less than 0.05 was considered statistically significant. Results: This study included 1000 participants. 70.7% reported that their oral-health care practices became worse during the COVID-19 pandemic. Participants’ medical histories revealed that 17.8% had multiple chronic illnesses. Of all respondents, 48.2% believed that COVID-19 is a serious health problem and only 33.4% of respondents were aware that only emergency treatment is being offered at dental clinics during the COVID-19 pandemic. Conclusions: An alarming percentage of participants do not see COVID-19 as threatening to their health. A number of people needed urgent treatment but preferred to stay home because of fear and anxiety connected to the pandemic. The lack of information can lead to the exacerbation of such fear, which in turn causes individuals to neglect their oral health.